Cabaran dalam mengekalkan warisan opera Cina dalam kalangan masyarakat Cina di Kuching : kajian kes di Persatuan drama Hokien Yi Sing - Tan, Ang Pang (Universiti Malaysia Sarawak (UNIMAS), 2004)
The aim of this research is to examine the challenges facing the Yi Sing Fukien Dramatic Association in their efforts to preserve the traditional of Chinese Opera among the Chinese community in Kuching. This research also looks at the strategies used by the Yi Sing Association to preserve Chinese Opera in Kuching. Hopefully this research will contribute to the new generation's appreciation of the art, culture and heritage of their forefathers.